Self-assembly of a "cationic-cage" via the formation of Ag–carbene bonds followed by imine condensation. Issue 47 (23rd May 2019) - Modak, Ritwik; Mondal, Bijnaneswar; Howlader, Prodip; Mukherjee, Partha Sarathi
Abstract : We develop a new strategy for the synthesis of a "cationic-cage" (CC-Ag ) via metal–carbene (M–CNHC ) bond formation followed by imine condensation. While the aldehyde alone doesn't yield the desired cage with the amine, Ag–NHC bond formation allows such condensation, leading to the formation of a "cationic-cage". Abstract : A new strategy for the synthesis of a "cationic-cage" (CC-Ag ) has been developed via metal–carbene (M–CNHC ) bond formation followed by imine bond condensation. Reaction of a trigonal trisimidazolium salt H3 L (PF6 )3 functionalized with three flexible N -phenyl-aldehyde pendants with silver oxide yielded a trinuclear tricationic organometallic cage (OC-Ag ). Subsequent treatment of the organometallic cage (OC-Ag ) with 1, 4-diaminobutane links the two tris–NHC ligands via imine bond condensation, which thus generates a 3D 'cationic-cage' (CC-Ag ). Furthermore, post-synthetic replacement of the Ag(i ) with Au(i ) leading to the formation ofCC-Au was achieved via trans -metalation, with the retention of the molecular architecture.